A novel role of helix‐loop‐helix transcriptional factor Bhlhe40 in osteoclast activation. Issue 10 (31st July 2022) - Hirata, Hirohito; Kamohara, Asana; Murayama, Masatoshi; Nishioka, Kenichi; Honda, Hiroaki; Urano, Yasuteru; Soejima, Hidenobu; Oki, Shinya; Kukita, Toshio; Kawano, Shunsuke; Mawatari, Masaaki; Kukita, Akiko
Abstract: The basic helix‐loop‐helix transcriptional factor, Bhlhe40 has been shown as a crucial regulator of immune response, tumorigenesis, and circadian rhythms. We identified Bhlhe40 as a possible regulator of osteoclast differentiation and function by shRNA library screening and found that Bhlhe40 was required for osteoclast activation. Bhlhe40 expression was induced in bone marrow macrophages (BMMs) by RANKL, whereas the expression of its homolog Bhlhe41 was decreased in osteoclastogenesis. μCT analysis of tibias revealed that Bhlhe40 knockout (KO) mice exhibited increased bone volume phenotype. Bone morphometric analysis showed that osteoclast number and bone resorption were decreased in Bhlhe40 KO mice, whereas significant differences in the osteoblast parameters were not seen between wild‐type (WT) and Bhlhe40 KO mice. In vitro culture of BMMs showed that Bhlhe40 deficiency did not cause difference in osteoclast formation. In contrast, bone resorption activity of Bhlhe40 KO osteoclasts was markedly reduced in comparison with that of WT osteoclasts. Analysis of potential target genes of Bhlhe40 using data‐mining platform ChIP‐Atlas (http://chip-atlas.org ) revealed that predicted target genes of Bhlhe40 were related to proton transport and intracellular vesicle acidification. We then analyzed the expression of proton pump, the vacuolar (V)‐ATPases which are responsible for bone resorption. The expression of V‐ATPases V1c1 and V0a3 was suppressed in Bhlhe40 KO osteoclasts. In addition, Lysosensor yellow/blue DND 160 staining demonstrated that vesicular acidification was attenuated in vesicles of Bhlhe40 KO osteoclasts. Furthermore, analysis with pH‐sensitive fluorescent probe showed that proton secretion was markedly suppressed in Bhlhe40 KO osteoclasts compared to that in WT osteoclasts. Our findings suggest that Bhlhe40 plays a novel important role in the regulation of acid production in osteoclastic bone resorption. Abstract : Transcriptional factor Bhlhe40 plays a novel role in osteoclast function. Bone resorption activity and proton production were suppressed in Bhlhe40 knockout (KO) osteoclasts. Analysis by data‐mining platform ChIP‐Atlas revealed that predicted target genes of Bhlhe40 are related to proton transport, and expression of V‐ATPases was reduced in Bhlhe40 KO osteoclasts.